The convergence of social networks and radio as a significant environment in non-formal educationgnificativo en la educación no formal - Solís Muñoz, Juan (Universidad Nacional de Córdoba, Faculdad de Ciencias Sociales, Centro de Estudios Avanzados. Maestría en Procesos Educativos Mediados por Tecnología, 2016)
This article defines a technical-communicational model that proposes a converg ence area for educational purposes, between traditional communication media and social networks. The analysis is developed on the basis of the experience from a university radio media (Ondas Cañaris of the Catholic University of Cuenca-Ecuador) in convergence with Facebook in order to promote content-producing audiences. A new citizen role that implies education and communication is proposed. According to this new role, the radio population segments make use of their right to communicate from their realities and educate the audience respecting their identity. Finally, from three programs and three profiles of audience participation, conclusions are derived both from the theoretical positions and from the research process of the analyzed implementation.